Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone